REFLECTIONS ON THE EVOLUTION OF MINOR'S RIGHTS IN CONFLICT WITH THE LAW IN THE EUROPEAN UNION: FROM THE NATIONAL REGULATIONS TO THE COMMUNITY REGULATIONS - Gheorghe, BONCIU (Strategii Manageriale, 2015)
The study proposes an examination of the development rights of juveniles in conflict with the law in terms of legal regulations adopted by the Council of Europe, the European Union and its Member States. Approaching the settlement of all matters relating to human rights, including the rights of the child, it searched the extent to provide a mechanism in respect of children's rights and how its rights are reflected both of the European Convention on Human Rights and Fundamental Freedoms and Community and of national regulations of the Member States of the European Union. Declarative character of the Community provisions do not provide sufficient protection and uniformity toward juvenile rights in this matter, being treated differently in different countries depending on national and regional legal regime. Analysis of international treaties, customary, and national case law emphasized the need for prevention of juvenile delinquency and juvenile protection by merging rules at Community level in order to ensure a common, reasonable and sufficient protection for the juvenile in general and those found in conflict with law in particular.